COMBINATION OF ISOTONIC LEBIH BAIK DARIPADA RHYTHMIC STABILIZATION DALAM MENURUNKAN DISABILITAS PENGRAJIN GENTENG PADA KONDISI NYERI PUNGGUNG BAWAH MIOGENIK DI DESA DARMASABA - Andrini, Dewa Agung Gina; Adiputra, N.; -, Wahyuddin; Purnawati, Susy; Linawati, Ni Made; -, Sugijanto (Sport and Fitness Journal; Volume 5, No.3, 2017, 2017)
Background: Myogenic low back pain is pain around of the lower back muscle or a disorder caused by abnormalities in the musculoskeletal system without neurological disorders.Combination of isotonic and rhythmic stabilization is PNF exercises that commonly used in the treatment of myogenic low back pain. Purpose : The purpose of this study prove that the combination of isotonic better than rhythmic stabilization to decrease disability in craftsman tile with myogenic low back pain in Darmasaba village. Methods: This study uses an experimental design with pre-test and post-test control group design. The experiment was conducted in Darmasaba village and subjects were 20 patients.Decreased disability was measured with the Modified Oswestry Disability Index (MODI) before and after training. Results: Statistical test results obtained, a decrease in MODI scores in the first treatment group showed that mean difference obtained 38.20±3.048 and for the second group obtained 31.80±4.050 with p=0.001. Conclusion: From these results it can be concluded that the combination of isotonic is better than rhythmic stabilization for decreased disability of tile craftsman with myogenic low back pain in Darmasaba village. Suggestion: For the next researcher can do follow up research to see long-term result of combination of isotonic and rhythmic stabilization for tile craftsman.